EXPLORING CHALLENGES ENCOUNTERED BY NOVICE FEMALE TEACHERS REGARDING CLASSROOM MANAGEMENT IN SECONDARY SCHOOLS - Saltiel Khololo Collen Matabogei (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2024)
The authors' purpose through this conceptual paper is to explore the challenges novice female teachers encounter in classroom management within secondary schools. The main question guiding this research is: "What are the specific classroom management difficulties faced by novice female teachers in secondary school settings?" A qualitative approach is employed, using recent literature reviews encompassing scholarly books and articles published between (2018-2024 on the perspectives of authors regarding the topic under discussion. This study is grounded within an interpretive paradigm which provides deeper insight into the scholarly perceptions regarding the topic under discussion. The findings reveal that novice female teachers often struggle with maintaining discipline, establishing authority and balancing relationships with students. Similarly, issues related to gender dynamics and societal expectations further exacerbate their classroom management strategies. Notably, this study is significant as it contributes to the existing body of knowledge on gender-specific challenges in education providing insights for teacher training programs and policy adjustments. Nonetheless, the limitations of this study include its focus on a single case study and its reliance on qualitative data which may not be generalizable to all contexts. Thus, further research is recommended to explore broader patterns across different school environments.